â€œI BELIEVE RELATIONSHIPS MATTER EVERYWHEREâ€ THE IMPACT OF RELATIONSHIPS WELL-BEING IN INTERCULTURAL THEMATIC-TELECOLLABORATION - Almas Khoirun Nisa; Nur Arifah Drajati (IAIN Syekh Nurjati Cirebon, 2024)
Relationships among students and teachers are important in a learning environment since teachers and students are the main components of learning activities. Telecollaboration attempts to connect language learners to native speakers in the online environment to facilitate their intercultural learning. As online learning activities need to pay attention to the relationship between the teacher and learner, this study investigates the impact of the relationship well-being that occurs in the telecollaboration program on the pre-service teacher’s future career. An autobiographical narrative inquiry was used in this study for an in-depth discussion of the critical incidents that happened in this program aimed to give the pre-service teachers insight for developing their professional identity in their future careers for the betterment of EFL education. Data were collected through the pre-service teacher’s diaries and artifacts in the form of photos during the telecollaboration program. Various issues of critical incidents are discussed including positive relationships and negative relationships reflected in the pre-service teacher’s future career that turn into adaptive reflection. This study has future implications for pre or in-service EFL teachers and directions for future research to pay more attention to the well-being of all aspects of education.